PENGARUH BERBAGI PENGETAHUAN DENGAN METODE STORYTELLING UNTUK MENINGKATKAN KESIAPAN UNTUK BERUBAH PADA KARYAWAN - , Diar Kusumawati, Rahmat Hidayat, S.Psi, M.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aimed at investigating the effect of sharing knowledge with storytelling to increase employeesâ readiness to change. The research involved 32 people divided into two groups: an experimental group (16 persons) and control group (16 people. The research was conducted by comparing two groups: experimental group receiving storytelling about five messeges to change with control groups that do not get treatment. Respondents were civil servants. The design of experiments using a pretest-posttest control group design. Level of readiness to change is measured using readiness to change scale. Measurements were taken before the intervention and after the intervention. The result shown that storytelling was effective to increase readiness to change for employee with organizational change (F = 71.24, p <0.01)